A Study of the Cognitive Development of Hispanic Adolescents Learning Algebra Using Clinical Interview Techniques. Final Report - Gerace, William J.; Mestre, Jose P.; Massachusetts Univ., Amherst. Dept. of Physics and Astronomy ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
This document reports in detail an investigation of the cognitive processes and learning difficulties of ninth-grade students in Algebra I. A clinical interview approach was used with 14 students. A group of six Hispanic students and a group of five Anglo students were enrolled in the same algebra class; a group of three Hispanic students who had begun algebra one-half year earlier was also included. Probed were students' appreciation of algebra as an abstract logical system, command of the formal operations of algebra, ability to use algebra, and ability to solve problems. Performance in English vs. Spanish was compared, and students' teaching styles were analyzed as they taught peers. It was found that students preferred not to use algebraic techniques in solving problems, were poor at verbalizing definitions and procedures and at translating problem statements into equations, did not use their textbooks very much except as a place to find assigned problems, and treated algebra as a rule-based discipline, not as a concept-based one. Detailed descriptions of student performance are given, and findings are discussed in relation to textbooks, pedagogy, linguistics, and directions for future research. Nine recommendations for improved pedagogy and learning are also presented. Questions asked in eight interview sessions are appended, as is selected background information on student participants. (MNS)
Sponsoring Agency: National Inst. of Education (ED), Washington, DC.
Contract Number: 400-81-0027.
ERIC Note: For summary of this document, see SE 041 616.
Educational level discussed: Grade 9.
Educational level discussed: Secondary Education.
Practitioners.
Keywords: Algebra; Cognitive Processes; Educational Research; Grade 9.; Hispanic Americans; Interviews; Language Role; Learning Problems; Mathematics Instruction; Minority Groups; Problem Solving; Secondary Education; Secondary School Mathematics; Teaching Methods; Textbooks; Mathematics Education Research; Reports, Research